Automobile Purchase-peer Influence in Decision Making - Clement Sudhahar, J.; Venkatapathy, R. (Indian Journal of Marketing, 2005)
The overall economic development of a country is determined by the development in Manufacturing sector. Similarly, the quality of life to a great extent depends upon the growth and development in Consumer luxury goods segment. Though the entry of quality luxury goods in India is late, to be precise only after the liberalization, still India is competing with top nations in terms of range and quality of such goods. Urbanization and metropolitan culture have necessitated the need for Fast foods, Designer clothes, Luxury cars, Modern flats etc. Added to this, the change in the family and in earning pattern, especially the emergence of Double Income Group families have resulted in significant changes in the buying behaviour of individuals.